How full is full? : comparing bodies of water - Parker, Victoria (Chicago : Heinemann Library, 2011)
Applies the math functions of measuring and comparing to bodies of water, and includes an activity and fullness quiz.
Measuring capacity -- What is a body of water? -- A glass of water -- A bath -- A fish pond -- A swimming pool -- A canal lock -- A reservoir -- A lake -- A sea -- An ocean -- Measuring activity.
Includes bibliographical references (p. 31) and index.
Library Media Connection
Wilson's Children
Library Media Connection, March 2011
Wilson's Children, September 2011
3.0
Keywords: Volume (Cubic content) -- Juvenile literature; Volume (Cubic content); Volume (Cubic content)